2014
DOI: 10.1016/j.vaccine.2014.07.113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in vitro evolution on antigenic diversity of Mycobacterium bovis bacillus Calmette-Guerin (BCG)

Abstract: Mycobacterium bovis bacillus Calmette-Guerin (BCG), the only vaccine currently used against tuberculosis, is an attenuated derivative of M. bovis that has been propagated in vitro for more than 40 years. We have previously reported that the experimentally-verified human T cell epitopes of the M. tuberculosis complex (MTBC) are the most conserved elements of the genome; whether immune recognition is the force driving the conservation of epitopes in the MTBC is unknown. Therefore, we sequenced the genomes of 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 36 publications
2
61
0
2
Order By: Relevance
“…The majority (82%) of these absent epitopes are contained in 6 antigenic proteins encoded in RD1 and RD2 deleted in BCG strains. These and related studies further suggested that epitope sequence variation in BCG potentially affects human T cell recognition that could result in ineffective priming of the host immune system [16,17,[50][51][52].…”
Section: The Current Clinical Tb Vaccine Pipelinementioning
confidence: 89%
See 2 more Smart Citations
“…The majority (82%) of these absent epitopes are contained in 6 antigenic proteins encoded in RD1 and RD2 deleted in BCG strains. These and related studies further suggested that epitope sequence variation in BCG potentially affects human T cell recognition that could result in ineffective priming of the host immune system [16,17,[50][51][52].…”
Section: The Current Clinical Tb Vaccine Pipelinementioning
confidence: 89%
“…It is generally well assumed that T cell epitopes are evolutionarily conserved in the MTBC [48,49]. Copin et al [50] compared the sequence diversity of 1530 experimentally verified human T cell epitopes and found that 23% of the known MTBC T cell epitopes are absent in BCG. The majority (82%) of these absent epitopes are contained in 6 antigenic proteins encoded in RD1 and RD2 deleted in BCG strains.…”
Section: The Current Clinical Tb Vaccine Pipelinementioning
confidence: 99%
See 1 more Smart Citation
“…The genome sequences of different BCG strains were compared to determine T-cell epitope conservation (47). It was found that among the 1,530 human T-cell epitopes, 23% of them are absent in the BCG vaccines.…”
Section: Bcg: the Only Vaccine In Use To Prevent Disseminated But Notmentioning
confidence: 99%
“…It was found that among the 1,530 human T-cell epitopes, 23% of them are absent in the BCG vaccines. The majority of the absent epitopes in BCG are contained in three proteins: ESAT-6, CFP-10 (10-kDa culture filtrate protein), and PPE68 (cell envelope protein from PPE family that contributes to M. tuberculosis maintenance of infection) all of them encoded in the RD1 region absent in BCG (47). If these epitopes are necessary to complete the pulmonary cycle of M. tuberculosis, we could hypothesize that vaccine candidates containing epitopes absent in BCG could confer immunity to protect against pulmonary TB.…”
Section: Bcg: the Only Vaccine In Use To Prevent Disseminated But Notmentioning
confidence: 99%